Study to assess the effectiveness of lamaze method on mode of labour among primigravid women at selected setting -pilot study - MRS.T.MAHALAKSHMI; DR.HEPZIBA KIRUBAMANI (International Journal of Pharma and Bio Sciences, 2017)
A key component to prenatal care is childbirth education, although many women do not receive any formalized preparation. Multiple models of Child birth education for both within health care settings, including such as Lamaze and Bradley. A birth plan as a component of childbirth preparation, can be a medium to improve patient-provider communication regarding a desired labor and birth experience and improve satisfaction with care. Lamaze childbirth method is the method which prepares a woman for coping with stressful birthing process. The study was aimed to determine the effectiveness of Lamaze method on mode of labour among primigravid women in experimental group& to compare the mode of labour between experimental &control group mothers. A research design adopted for this study was True experimental design. The primigravida mothers with Last menstrual period (LMP) from may last to June I week were chosen as sample in this study. The total sample size were 24 chosen for this study, 12 in control group (Primi gravid mothers) they were taken in Kolathur health post & 12 experimental group samples were taken in Ayanavaram health post . Sample was selected by using simple random sampling technique. Data were analyzed by using descriptive and inferential statistics. The study findings concluded that childbirth preparedness class is a great way to prepare mother for labor and birth. It provide with information to minimize fears and help to make informed decisions as well as help to relax and cope with childbirth experiences.